Anatomic types of anomalous aortic origin of a coronary artery: A pictorial summary. (24th July 2017) - Agrawal, Hitesh; Mery, Carlos M.; Krishnamurthy, Rajesh; Molossi, Silvana
Abstract: Anomalous aortic origin of a coronary artery is a congenital abnormality of the origin or course of a coronary artery that arises from the aorta. As commonly seen in congenital heart disease, a wide spectrum of anatomic variability is seen and hence, it is important for clinicians to document the precise anatomy and course of the anomalous vessel. This article describes coronary artery nomenclature using computerized tomography angiography and virtual angioscopy. These details are important for decision making, useful for surgical planning, and may have prognostic implications.